2023
DOI: 10.1128/spectrum.00904-23
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Mediation Effects between Intratumoral Microbiome and Host DNA Methylation Changes Contribute to Stomach Adenocarcinoma

Abstract: The burgeoning field of oncobiome research declared that members of the intratumoral microbiome besides Helicobacter pylori existed in tumor tissues and participated in the occurrence and development of gastric cancer, and the methylation of host DNA may be a potential target of microbes and their metabolites. Current research focuses mostly on species composition, but the functional genes of the members of the microbiota are also key to their interaction with the host.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…As for the mechanism, many studies have revealed that non- H. pylori microorganisms promote GC by inducing inflammation, modulating the immune response, triggering DNA damage, and promoting epithelial–mesenchymal transformation ( Yang et al, 2022 ; Liao et al, 2023 ). Gastric non- H. pylori microorganisms may participate in the progression of GC by affecting host DNA methylation ( Yue et al, 2023 ). Different bacterial taxa are related to certain types of infiltrating immune cells ( Liao et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…As for the mechanism, many studies have revealed that non- H. pylori microorganisms promote GC by inducing inflammation, modulating the immune response, triggering DNA damage, and promoting epithelial–mesenchymal transformation ( Yang et al, 2022 ; Liao et al, 2023 ). Gastric non- H. pylori microorganisms may participate in the progression of GC by affecting host DNA methylation ( Yue et al, 2023 ). Different bacterial taxa are related to certain types of infiltrating immune cells ( Liao et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Helicobacter pylori is an ITM known to promote gastric cancer and affects tumors mainly through methylation. By screening methylation pathways H. pylori was observed to be highly enriched in gastric cancer, and cellular experiments have shown that Staphylococcus saccharolyticus promotes gastric cell proliferation and cloning by regulating the gene expression level of the zinc finger protein 215 gene 42 . Thus, screening for methylation pathways may be a potential metabolic target to identify gastric cancer.…”
Section: Itm Identification For Tumor Diagnosis and Stagingmentioning
confidence: 99%
“…In hepatocellular carcinoma, microbial α and β diversities are increased, with a significant increase in the abundance of microorganisms, such as Enterobacteriaceae, Clostridium , and Neisseria , and a decrease in the abundance of certain antitumor bacteria, such as Pseudomonas . In terms of metabolism, processes such as fatty acid and lipid synthesis are significantly enhanced in the microbiota of cancerous tissues 42 . Huang et al 42 have used the ITM model of liver cancer to differentiate between patients with liver cancer and healthy populations, which shows excellent performance with an area under the curve (AUC) of 0.968.…”
Section: Itm Identification For Tumor Diagnosis and Stagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, there is also much evidence showing that microbiome regulates the biology of cancer cells via epigenetic mechanisms. In stomach cancer, the intratumor microbiome, especially Kytococcus sedentarius and Actinomyces orisinteracted , was strongly associated with methylation changes in immune‐related genes of cancer cells and regulated gene expression 88 . In esophageal cancer, the presence of F. nucleatum was associated with LINE‐1 hypomethylation, which was associated with poor prognosis 89 .…”
Section: Mechanisms Of Intratumor Microbiome In Modulating Tumor Init...mentioning
confidence: 99%